Pemanfaatan Pangan Lokal Pada Demo Masak Menu Dapur Sehat Atasi Stunting Sebagai Inovasi Menu Bergizi Bagi Anak Stunting Kepada PKK Kelurahan Kauman Kidul - Amidi , Amidi; Tussaleha, Annisa; Firdaus , Wildanti Dian; Husada, Bayu (Jurnal Bina Desa, 2025)
Stunting is one of the serious health problems in the world. Insufficient nutritional intake is one of the main factors causing stunting in children. In Indonesia itself, precisely in Salatiga City in 2023 based on calculations from the e-PPBGM application, the prevalence of stunting has decreased by 43.72%. Meanwhile, the stunting rate in Kauman Kidul Village in 2024 was 24 children. With the high stunting rate in Kauman Kidul, Unnes Giat 9 students conducted a cooking demonstration of the Healthy Kitchen to Overcome Stunting (DASHAT) menu at the Kauman Kidul PKK. This cooking demonstration activity aims to increase awareness of the importance of balanced nutrition and knowledge about stunting in the community. The implementation of the cooking demonstration activity consists of the preparation stage and the implementation stage. The activity was filled with "Isi Piringku" education followed by a cooking demonstration. In the cooking demonstration, the main ingredients used in the DASHAT menu are local food ingredients that are easy to obtain. The use of local food ingredients is a form of utilizing resources that come from the surrounding area. By holding a cooking demonstration, it is hoped that it can increase knowledge, utilization, and creation of a balanced nutritional menu from local food ingredients.